2005
DOI: 10.1021/cm048050g
|View full text |Cite
|
Sign up to set email alerts
|

A Floating Self-Assembly Route to Colloidal Crystal Templates for 3D Cell Scaffolds

Abstract: Preparation of well-ordered three-dimensional (3D) scaffolds is of great importance for various aspects of tissue engineering and fundamental research in cell biology. A versatile technique, floating self-assembly, is reported here for the first time to prepare 3D colloidal crystals from polystyrene particles of various diameters (10-240 µm). Ethylene glycol was used as the solvent in the self-assembly process of colloidal crystals. Polymer colloidal particles float on the surface of ethylene glycol and self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 24 publications
0
67
0
2
Order By: Relevance
“…In addition to substrate patterning, electrostatic [48], external electric field [49,50], floating self-assembly [51], centrifugation [52], filtration [53], and other methods [54][55][56] have all been investigated as a means for colloidal particle assembly. For example, in Figure 5 [51,52] there are examples of three-dimensional structure obtained from floating self-assembly and centrifugation, respectively.…”
Section: Surface Pattern-assisted Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to substrate patterning, electrostatic [48], external electric field [49,50], floating self-assembly [51], centrifugation [52], filtration [53], and other methods [54][55][56] have all been investigated as a means for colloidal particle assembly. For example, in Figure 5 [51,52] there are examples of three-dimensional structure obtained from floating self-assembly and centrifugation, respectively.…”
Section: Surface Pattern-assisted Depositionmentioning
confidence: 99%
“…For example, in Figure 5 [51,52] there are examples of three-dimensional structure obtained from floating self-assembly and centrifugation, respectively.…”
Section: Surface Pattern-assisted Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of self-assembly approaches have been reported, including the assembly of particles with a range of sizes and shapes [21][22][23] . Special attention has been paid to the 'floating assembly' of micronanoparticles floating on liquid-air interfaces [24][25][26] , as this technique is technically relatively simple and produces high-quality monolayers or even 3D assemblies of particles. It has been reported that the success of the floating assembly results from the capillary forces between the floating particles 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Without ethylene glycol addition, the assembled pollen grains cracked after drying ( Figure S3 in the Supporting Information). We also tried other methods of self-assembly, such as vertical deposition, [16] floating self-assembly, [17] and liquid interface-mediated assembly, [18] but failed to assemble the pollen grains into a large-scale and crack-free pollen layer ( Figure S4 in the Supporting Information). These results show that a close-packed and large-scale pollen layer has been successfully fabricated by using the filtering-assisted assembly.…”
mentioning
confidence: 99%